Lysine supplementation of low-protein diets for finishing pigs - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1973)
Four experiments involving 311 finishing pigs (112 to 220 pounds) were conducted to determine the minimum level of soybean meal necessary to supply all essential amino acids except lysine that are deficient in milo or corn and to determine the influence of lysine supplementation of low protein diets for finishing pigs. The results of three trials using milo as the grain source demonstrated that pigs fed milo supplemented with 7.5% soybean meal and lysine gained at the same rate and were just as efficient in feed utilization as pigs fed milo supplemented with 15% soybean meal. Carcass composition as measured by backfat thickness, loin-eye area, and percentage of the carcass in ham and loin did not differ between pigs fed milo supplemented with 7.5% soybean meal and lysine and pigs fed the control diet containing 15% soybean meal. In the fourth trial with corn as the grain source, weight gain and feed efficiency of pigs fed corn supplemented with 7.5% soybean and lysine were equivalent to that of pigs fed the control diet containing 15% soybean meal. These results demonstrate that the amount of soybean meal in the diet of finishing pigs can be reduced approximately 50% by adding crystalline lysine with no detrimental effects on weight gain, feed efficiency, or carcass composition.; Swine Day, Manhattan, KS, November, 1973
Keywords: Swine day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 203; Swine; Lysine; Protein; Finishing pigs; Milo